Violence and Post-Traumatic Stress Disorder in Hannah Kent's Burial Rites - Fadilah Wipi; Ferdinal (Andalas International Journal of Socio-Humanities, 2022)
Many fields of study, including literary studies, pay a serious attention on the connection between violence and trauma. Responding to such an attention, this article aims to investigate some issues of violence and post-traumatic stress disorder represented in the novel Burial Rites by Hannah Kent. The writing is based on library research. This descriptive-qualitative study applies psychoanalysis theory by Sigmund Freud to analyze the representation of violence and post-traumatic stress disorder in the novel. The findings show that Kent, through Burial Rites, illustrates that the impacts of violence on someone can be both physical and psychological. Kent demonstrates a relationship between violence and post-traumatic stress disorder in the story. It depicts that the violence a person has experienced in life, whether physical or psychological, can cause a mental disorder called post-traumatic stress disorder. The illness can make the sufferers regularly experience fear, nightmares, anxiety, and other things that disturb their mind and soul.